2006
DOI: 10.1111/j.1524-6175.2006.05335.x
|View full text |Cite
|
Sign up to set email alerts
|

Physician Familiarity With Diagnosis and Management of Hypertension According to JNC 7 Guidelines

Abstract: Physician knowledge of the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7) guidelines is unknown and may contribute to the prevalence of uncontrolled hypertension. Our objective was to determine physician knowledge of JNC 7 guidelines and whether online instruction could improve knowledge. A pretest served as baseline knowledge, and comparison with a post-test after completing an online didactic demonstrated improvement in knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…To provide another approach that serves those who prefer in-person education, we will also employ educational sessions in small group settings to reinforce key content and guidelines [37]. Self-learning materials will also be used that contain the same content.…”
Section: Discussionmentioning
confidence: 99%
“…To provide another approach that serves those who prefer in-person education, we will also employ educational sessions in small group settings to reinforce key content and guidelines [37]. Self-learning materials will also be used that contain the same content.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent systematic review revealed that DHPs were inferior to non-DHPs in reducing proteinuria [7]. On the basis of these findings, the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7) guidelines recommends DHPs as a first-line therapy for patients with isolated systolic hypertension especially for the reduction of stroke and as an add-on agent to achieve optimal BP level in other hypertensive patients except for heart failure with systolic dysfunction [8]. NonDHPs, alone or in combination with ACEIs or ARBs, are suggested as preferred agents to lower BP in hypertensive patients with nephropathy associated with overt proteinuria [9].…”
Section: Introductionmentioning
confidence: 93%
“…10 Similar findings have been reported from developed countries. [11][12][13] We did this study in Karachi, Pakistan, to assess the impact of special educational training of general practitioners in the management of hypertension on adherence to prescribed antihypertensive drugs and to determine the practice patterns of doctors that contribute to adherence to antihypertensive drugs. We hypothesised that adherence to antihypertensive drugs by patients seeking care from general practitioners specially trained in the management of hypertension would be higher than in those seeking care from general practitioners providing usual care.…”
Section: Introductionmentioning
confidence: 99%